2016
DOI: 10.1103/physreve.94.042313
|View full text |Cite
|
Sign up to set email alerts
|

Input-output relationship in social communications characterized by spike train analysis

Abstract: We study the dynamical properties of human communication through different channels, i.e., short messages, phone calls, and emails, adopting techniques from neuronal spike train analysis in order to characterize the temporal fluctuations of successive inter-event times. We first measure the so-called local variation (LV) of incoming and outgoing event sequences of users, and find that these in-and out-LV values are positively correlated for short messages, and uncorrelated for phone calls and emails. Second, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…Karsai et al (2012a) used the data from a European operator (Onnela et al, 2007b) to show that α ≈ 0.7 for calls and α ≈ 1.0 for SMSs. Aoki et al (2016) also used the data from a European operator (Tabourier et al, 2016) and found α to be 1.2 and 1.4 for calls and SMSs, respectively. Using a Chinese dataset, Jiang et al (2013) found that although the aggregate P (τ ) follows a power law, a majority of individual users show Weibull distributions for interevent times.…”
Section: Burstiness In the Time Series Of Human Communicationmentioning
confidence: 99%
“…Karsai et al (2012a) used the data from a European operator (Onnela et al, 2007b) to show that α ≈ 0.7 for calls and α ≈ 1.0 for SMSs. Aoki et al (2016) also used the data from a European operator (Tabourier et al, 2016) and found α to be 1.2 and 1.4 for calls and SMSs, respectively. Using a Chinese dataset, Jiang et al (2013) found that although the aggregate P (τ ) follows a power law, a majority of individual users show Weibull distributions for interevent times.…”
Section: Burstiness In the Time Series Of Human Communicationmentioning
confidence: 99%
“…[15, 18] to decide whether L V consistently characterizes the time series. This means that the variance of L V across different periods in one time series should be smaller than the variance in the population of all time series.…”
Section: Resultsmentioning
confidence: 99%
“…This means that the variance of L V across different periods in one time series should be smaller than the variance in the population of all time series. Here we subdivide each time series in 20 slices and calculate the corresponding F-values as the ratios between the variance of L V in the population of all time series and the variances across the 20 slices [15, 18]. For different popularity classes, we show the F-values of L V in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In that case, adopting a local perspective for the walker dynamics might prove useful to test the notion of anomalous diffusion [30]. Another possible application would the modelling of diffusion on temporal networks [31], especially in the presence of burstiness [32] and the number of events within a time window can be broadly distributed, possibly under the form of trains of events [33].…”
Section: Discussionmentioning
confidence: 99%